Cultivation Management: System of Rice Intensification (SRI) for Higher Production - Nur Badriyah Kamarul Zaman; Jamal Ali; Zakirah Othman (International Journal of Supply Chain Management, 2017)
Abstract Enhancing farm production through an application of sustainable agriculture innovation to the existing farm system is relevant to face the simultaneous challenge in achieving food security, land protection and soil fertility and improving the wellbeing of farmers especially in rural areas. The System of Rice Intensification (SRI) technique is one of the sustainable rice cultivation techniques that have been introduced with the aim of improving the lives of rural farmers in Malaysia. The study was carried out to examine the differences in the cost of operations, paddy production and profitability of farmers using SRI technique and farmers who use conventional technique. Cost and production analysis among farmers as rice producers are important to be highlighted because farmers are the main actor in rice industry supply chain. In order to improve rice industry supply chain, focus should be given to the farmers welfare. Profitability analysis using budget technique has been used in this study. The study found that SRI technique is very successful in increasing the productivity of rice production while reducing the cost of production thereby increasing the profitability of farmers. It is important to identify the economic benefits of using SRI technique as it will encourage the adoption of this technique among rural areas farmers. Keywords Supply chain, SRI practice, Cost and Benefit, SRI Practice, Innovation